The Routledge history of monarchy
1 online resource.
Keywords: "The Routledge History of Monarchy draws together current research across the field of royal studies, providing a rich understanding of the history of monarchy from a variety of geographical, cultural and temporal contexts. Opening up the discussion of important questions surrounding fundamental issues of monarchy and rulership, The Routledge History of Monarchy is the ideal book for students and academics of royal studies, monarchy, or political history"--